2018
DOI: 10.5194/acp-18-17909-2018
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical box modelling of volcanic SO<sub>2</sub> oxidation: isotopic constraints

Abstract: Abstract. The photochemical box model CiTTyCAT is used to analyse the absence of oxygen mass-independent anomalies (O-MIF) in volcanic sulfates produced in the troposphere. An aqueous sulfur oxidation module is implemented in the model and coupled to an oxygen isotopic scheme describing the transfer of O-MIF during the oxidation of SO2 by OH in the gas-phase, and by H2O2, O3 and O2 catalysed by TMI in the liquid phase. Multiple model simulations are performed in order to explore the relative importance of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 140 publications
(203 reference statements)
2
20
0
Order By: Relevance
“…Coincident measurements of SO2 and aerosols near the vent of volcano likely reveal the interaction between water vapor, SO2 and aerosols (Roberts et al, 2018). In-cloud SO2 decreased rapidly probably because of different aqueous pathways leading to the formation of sulfate either from the oxidation of H2O2 (Carn et al, 2011), O3 and/or the TMI-O2 pathway (Galeazzo et al, 2018) even if we cannot rule out potential measurement artifacts of SO2 in high RH conditions. The vog was observed downwind from Fissure 8 across the Pacific Ocean.…”
Section: The Volkilau Campaign a Conceptmentioning
confidence: 93%
See 2 more Smart Citations
“…Coincident measurements of SO2 and aerosols near the vent of volcano likely reveal the interaction between water vapor, SO2 and aerosols (Roberts et al, 2018). In-cloud SO2 decreased rapidly probably because of different aqueous pathways leading to the formation of sulfate either from the oxidation of H2O2 (Carn et al, 2011), O3 and/or the TMI-O2 pathway (Galeazzo et al, 2018) even if we cannot rule out potential measurement artifacts of SO2 in high RH conditions. The vog was observed downwind from Fissure 8 across the Pacific Ocean.…”
Section: The Volkilau Campaign a Conceptmentioning
confidence: 93%
“…Roberts et al (2019) recently showed through kinetic-based simulations that high temperature chemistry quickly forms oxidants such as OH, HO2 and H2O2 that can lead to the production of sulfate within a few second after the emission of SO2 starts. The aqueous pathways for sulfate formation have been studied with photochemical model including isotope markers showing that TMI (Transition Metal Ion)-O2 could indeed dominate the formation of sulfate (Galeazzo et al, 2018) relative to other pathways through H2O2 and O3, which can be rapidly titrated at low pH. In addition, the production of sulfate through new particle formation has been shown to be more frequent under the influence of volcanic emissions compared to background level conditions (Rose et al, 2019, Boulon et al, 2011, Sahyoun et al, 2019.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lifetime of SO 2 in the lower troposphere is generally considered to be on the order of 1-3 days to a week (Allen et al, 2002;Rotstayn and Lohmann, 2002;Pfeffer et al, 2006a;Pattantyus et al, 2018), the rate of conversion depending on relative humidity and temperature, the availability of oxidants, and interaction with cloud or fog (Saxena and Seigneur, 1987;Oppenheimer et al, 1998). However, the SO 2 oxidation pathways in a volcanic cloud are not necessarily the same as under background conditions (Galeazzo et al, 2018). Through a variety of reaction pathways (including oxidation with the hydroxyl radical, OH, and with hydrogen peroxide, H 2 O 2 , and O 3 ), SO 2 in volcanic clouds is gradually converted to sulfate aerosol (Stockwell and Calvert, 1983;Allen et al, 2002), which is a dominant component of volcanic PM 2.5 (Tam et al, 2016;Pattantyus et al, 2018).…”
Section: Dispersal Of Volcanic Emissionsmentioning
confidence: 99%
“…However, sulfate aerosols reduce the nucleation rate of ice crystals, affecting the properties of the ubiquitous upper troposphere cirrus clouds that play a critical role in climate (Kuebbeler et al, 2012). The properties of low-altitude meteorological clouds, their formation, lifetime and precipitation can be also substantially affected by the presence of volcanic sulfate aerosols in the lower troposphere, that are issued from persistent passive degassing activity (Gassó, 2008;Schmidt et al, 2012;Ebmeier et al, 2014) or from effusive eruptions (Yuan et al, 2011;McCoy and Hartmann, 2015;Malavelle et al, 2017).…”
Section: Introductionmentioning
confidence: 99%